Device for determining antifreeze freezing point - Anatychuk , L.I.; Havrylyuk, M. V. (Journal of Thermoelectricity, 2022)
The results of the development of the device for experimental measurement of antifreeze freezing point are provided. The device applies a direct measurement of antifreeze temperature upon its cooling to the freezing point using a thermoelectric module. An optimized heat exchange system, which has contributed to the development of a compact inexpensive device, available both to ordinary car enthusiasts and entrepreneurs dealing with car maintenance services, is used in the device design.